In vitro Effect of Low-level Lasers on Proteomic Concentration in Human Blood Plasma Using 375 nm and 650 nm Lasers - Ahmed Abdulkareem Al-Kaabi; Mustafa Al-Mosawi; Ali Abdullateef Abdulateef Al-Bayati (Mustansiriya Medical Journal, 2024)
Background: As a continuation of earlier laboratory research and its findings, we are studying the effects of biostimulation and alteration on human blood plasma to improve blood circulation in blood vessels, treat some infections, and treat various diseases, including blood protein-related ones. Methods: Blood samples were collected through venipuncture into tubes containing, ethylenediaminetetraacidic as an anticoagulant from healthy adult donors, and plasma was separated from blood components. Blood plasma samples were irradiated for varying periods (5, 10, 15, and20) min. Before and after irradiation, total protein and albumin concentrations were calculated using 375 nm and 650 nm lasers. Using a spectrophotometer, the concentration of total protein and albumin was determined for each sample. Results: At the (375 and 650) nm laser wavelength and exposure durations of (5, 10, 15, and 20) min, it was observed that the total protein concentration had significant differences between pre- and postirradiation probate value (P = 0.05, P = 0.05, P = 0.05, and P = 0.05, respectively). It was observed that the total protein and albumin concentrations had significant differences between pre- and postirradiation. In addition, the results demonstrate that the concentration of total protein and albumin decreases more significantly at a laser wavelength of 650 nm compared to a laser wavelength of 375 nm at times of (5 and 10) min. Conclusions: Our results clearly indicate that low-level lasers with different wavelengths of ( 375 , 630) nm both affect the concentration of total protein and albumin in human blood plasma, which can contribute to the treatment of many pathological conditions in the future.